Alum/Toll-Like Receptor 7 Adjuvant Enhances the Expansion of Memory B Cell Compartment Within the Draining Lymph Node - Vo, Hoa Thi My; Baudner, Barbara Christiane; Sammicheli, Stefano; Iannacone, Matteo; D’Oro, Ugo; Piccioli, Diego (Frontiers in Immunology, 2018)
Vaccination is one of the most cost-effective health interventions and, with the exception of water sanitization, no other action has had such a major effect in mortality reduction. Combined with other approaches, such as clean water, better hygiene and health education, vaccination contributed to prevent millions of cases of deaths among children under five years of age. New or improved vaccines are needed to fight some vaccine-preventable diseases that are still a threat for the public health globally, as reported also in the Global Vaccine Action Plan (GVAP) endorsed by the World Health Assembly in 2012. Adjuvants are substances that enhance the effectiveness of vaccination, but despite their critical role for the development of novel vaccines, very few of them are approved for use in humans. Aluminium hydroxide (Alum) is the most common adjuvant used in vaccines administered in millions of doses around the world to prevent several dangerous diseases. The development of an improved version of Alum can help to design and produce new or better vaccines. Alum/TLR7 is a novel Alum-based adjuvant, currently in phase I clinical development, formed by the attachment of a benzonaphthyridine compound, TLR7 agonist, to Alum. In preclinical studies, Alum/TLR7 showed a superior adjuvant capacity, compared to Alum, in several disease models, such as meningococcal meningitis, anthrax, staphylococcus infections. None of these studies reported the effect of Alum/TLR7 on the generation of the B cell memory compartment, despite this is a critical aspect to achieve a better immunization. In this study, we show, for the first time, that, compared to Alum, Alum/TLR7 enhances the expansion of the memory B cell compartment within the draining lymph node as result of intranodal sustained proliferation of antigen-engaged B cells and/or accumulation of memory B cells. In addition, we observed that Alum/TLR7 induces a recruitment of naïve antigen-specific B cells within the draining lymph node that may help to sustain the germinal center reaction. Our data further support Alum/TLR7 as a new promising adjuvant, which might contribute to meet the expectations of the GVAP for 2020 and beyond.